PERLINDUNGAN HUKUM TERHADAP TERSANGKA PADA TAHAP PENYIDIKAN YANG TDAK SESUAI DENGAN PASAL 52 KITAB UNDANG-UNDANG HUKUM ACARA PIDANA (contoh kasus: penangkapan tersangka pemilik ribuan rokok illegal) - Andri Tjhin; Mety Rahmawati (Jurnal Hukum Adigama, 2018)
Human rights are the rights attached to every individual and recognized by international law, in practice regarding human rights is regulated to become more specific, namely being the right of the suspect. The KUHAP regulates the rights of suspects precisely in Article 50 until 68. In the case of writing this scientific paper, there are several suspect rights in the stage of investigations that are violated by law enforcement officers, especially article 52, which means there are differences between those stipulated in the law with reality. The research method used is a normative legal research method which is based on primary, secondary, and supported by the results of interviews with related professions, which are then analyzed deductively. The results of this study illustrate that there is legal uncertainty amid law enforcement in Indonesia. Theory of justice, Theory of legal protection and the theory of legal certainty used which essentially becomes a benchmark for conformity of law enforcement in Indonesia.